The Utilization of TikTok Shop as a Promotion Platform and Real-Time Interaction with Consumers - Rahman, Shinta Abdul; Mafinanik, Hanisa; Febrianti, Niaqar; Murni, Nanda; Purwanto, Fadli Nurgamma; Akbar, Akbar; Rumadai, Muhamad Fadlan; Karim, Abdul (Fakultas Ekonomi dan Bisnis Islam Universitas Al- Hikmah Indonesia - Jurnal Ekonomi Pengabdian Masyarakat, 2024)
The Student Work Practice Program (PKM) aims to provide outreach to the public about the use of TikTok Shop as a potential digital platform for product marketing, especially for Micro, Small and Medium Enterprises (MSMEs). The activity was held on Monday, October 21 2024 at 16.00 WIT at the Babul Khair Mosque, with permission from Ustadz Arie as head of the mosque takmir. The methods used include presentations, live demonstrations of creating an account and uploading products on the TikTok Shop, as well as a question and answer session to answer participants' problems. The results of the activity showed that participants, especially MSME players, experienced an increased understanding of the steps to use TikTok Shop to develop their business. However, some participants still need further training regarding creative content strategy and digital marketing. This activity succeeded in making a positive contribution in increasing digital literacy among MSMEs, thereby encouraging them to be more adaptive to developments in digital technology in business.